Capacidad de adsorción de arsénico mediante isotermas de Langmuir y Freundlich en los suelos de la reserva ecológica los Ilinizas en la provincia de Cotopaxi durante el periodo 2020- 2021. - Lasluisa Chacha, Andrés Sebastián (2021)
One of the most toxic metalloids that is present in the environment is arsenic since its transition movement in the environment is very accessible because it shows high concentrations in bodies of water and soil, and this leads to both the population and the environment are in a deplorable state, and certain species cannot grow in soils that contain a greater amount of arsenic or that develop with a certain arsenic content; also, the population that is inhabiting this kind of places can be affected with health problems; therefore, the objective of this research is to determine the adsorption capacity in the soil of the Ilinizas ecological reserve around the hot springs in which were taken 22 samples according to the sampling criteria of TULSMA, Book VI Annex 2; to analyze these samples, the arsenic present was measured with the colorimetric method, later they were contaminated with arsenic in the different samples to use the method of the Langmuir and Freundlich isotherms, so the necessary agitation flow was used with a solution of 0.05 ml / l with a volume of 250 ml of arsenic solution, the adsorption through isotherms was evaluated working with different times of 0.05h to 24h resulting in a complete solution in the adsorbent in the Langmuir isotherm (r2 = 0.9112) which is an acceptable correlation, and maximum adsorbed amount of arsenic of 2.27 in the points while in the Freundlich isotherm (r2 = 0.8549) that is not so acceptable, and its margin of error is greater in almost the 22 samples which means that these data are not acceptable for the model in the monolayer because the maximum adsorbed amount of arsenic of -1.9728 is shown since in the study the Langmuir Isotherm is more acceptable because its margin of error is simply given in 3 samples than Freundlich, and this may be due to the fact that the adsorbent results of its pH range between 5.54 and 8.19 which indicates that it will have maximum retention, in addition to the Fe found in this soil with a maximum of 1255 ppm that causes the retention of arsenates and arsenites.